Hanna-McCormick family papers - Hanna, Marcus Alonzo, 1837-1904.; McCormick, Medill, 1877-1925.; Simms, Ruth Hanna McCormick, 1880-1944.
Correspondence, diary and notebook fragments, speeches, financial records, scrapbooks, printed matter, and other papers focusing chiefly on the political activities of Ruth Hanna McCormick Simms. Includes material concerning her congressional campaigns, activities on behalf of the Republican National Committee, work as presidential campaign manager for Thomas E. Dewey in 1944, and her reaction to economic depression and war. Marcus Alonzo Hanna's correspondence relates mainly to Ohio and national politics and also to his personal and business affairs. Includes copies of interviews (1905-1906) about him conducted by James B. Morrow with Joseph Benson Foraker, Theodore Roosevelt, and members of Hanna's family. Medill McCormick's papers relate to Illinois and national politics. Also includes papers relating to the Chicago Tribune and its publishers, Joseph Medill and Robert Rutherford McCormick, grandfather and brother of Medill McCormick. Family papers include correspondence between Ruth Hanna McCormick Simms and her daughter, Ruth McCormick Tankersley, known as Bazy.
Hanna's correspondents include his wife, Augusta Rhodes Hanna, and their daughter, Ruth Hanna McCormick Simms; and Benjamin Butterworth, J.C. Donaldson, Joseph Benson Foraker, Charles Foster, William McKinley, John Sherman, and John Wanamaker. Medill McCormick's family correspondents include his grandfather, Joseph Medill; mother, Katharine Medill McCormick; brother, Robert Rutherford McCormick; wife, Ruth Hanna McCormick Simms; and cousin, Joseph Medill Patterson. McCormick's other correspondents include Albert Jeremiah Beveridge, Edward Jackson Brundage, Calvin Coolidge, Joseph M. Dixon, Warren G. Harding, Charles Evans Hughes, Henry Cabot Lodge, Frank O. Lowden, William McKinley, Theodore Roosevelt, and George Richard Walker.
Family members represented include Marcus Alonzo Hanna (1837-1904), capitalist, political and presidential advisor, and U.S. senator from Ohio, also known as Mark Hanna; his daughter, Ruth Hanna McCormick Simms (1880-1944), U.S. representative from Illinois and political activist; and her first husband, Medill McCormick (1877-1925), publisher of the Chicago Tribune and U.S. representative and senator from Illinois, whose full name was Joseph Medill McCormick.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Brundage, Edward Jackson, -- 1869-1934 -- Correspondence; Butterworth, Benjamin, -- 1837-1898 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Dewey, Thomas E. -- 1902-1971.; Dixon, Joseph M. -- 1867-1934 -- Correspondence; Donaldson, J. C. -- Correspondence; Foraker, Joseph Benson, -- 1846-1917 -- Correspondence; Foraker, Joseph Benson, -- 1846-1917 -- Interviews; Foster, Charles, -- 1828-1904 -- Correspondence; Hanna, Augusta Rhodes, -- 1842?-1921 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Lowden, Frank O. -- 1861-1943 -- Correspondence; McCormick, Katharine Medill, -- 1853-1932 -- Correspondence; McCormick, Robert Rutherford, -- 1880-1955.; McCormick, Robert Rutherford, -- 1880-1955 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Medill, Joseph, -- 1823-1899.; Medill, Joseph, -- 1823-1899 -- Correspondence; Morrow, James B. -- 1855-1924.; Patterson, Joseph Medill, -- 1879-1946 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Interviews; Sherman, John, -- 1823-1900 -- Correspondence; Tankersley, Ruth McCormick, -- 1921- -- Correspondence; Walker, George Richard, -- 1857- -- Correspondence; Wanamaker, John, -- 1838-1922 -- Correspondence; Hanna family; Hanna family -- Interviews; McCormick family; United States. -- Congress -- Elections; United States. -- Congress. -- House; United States. -- Congress. -- Senate; Republican National Committee (U.S.); Republican Party (U.S. : 1854- ); Chicago tribune; American newspapers -- Illinois -- Chicago; Capitalists and financiers -- United States; Depressions; Newspaper editors -- Illinois -- Chicago; Newspaper publishing -- Illinois -- Chicago; Presidents -- United States -- Election -- 1944.; War; Women -- Political activity; Ohio -- Politics and government -- 1865-1950.; Illinois -- Politics and government -- 1865-1950.; United States -- Politics and government -- 1865-1933.; United States -- Politics and government -- 20th century